Employee Performance Optimization Through Work Discipline and Work Environment: Empirical Study in East Java Provincial Plantation Office - Rohyatul Hurpaini; Ilya Farida (PT. Anagata Sembagi Education, 2024)
This study is entitled employee performance optimization through work discipline and Work Environment : An Empirical Study in the East Java provincial plantation office. The purpose of this study was to determine and analyze how to improve the performance of employees through work discipline and work environment on the performance of employees in the Plantation Office of East Java province. The sampling method used is saturated samples. The sample in this study were 82 respondents. Data collection techniques with questionnaires. The Data used in this study is the primary data obtained through questionnaires. Instrument validity test using bivariate Correclation formula, while reliability test using Cronbach Alpha. Measuring instruments proved to be valid and reliable for research instruments. Multiple regression analysis was used to test the hypothesis of this study. The results showed that: the results of the F test Sig value of 0.001 ° 0.05. So it means that the variables of work discipline and work environment simultaneously affect employee performance variables. While the results of the T-test work discipline variables (X1) and work environment variables (X2) affect partially the performance of employees (Y) with a GIS value of 0.001 ° 0.05. Based on the results of the analysis it can be concluded that simultaneously or partially work discipline and work environment have a significant effect on the performance of employees in the Plantation Office of East Java province.